NATIONAL IMAGERY IN VISUAL ARTS: DIDACTIC MATERIALS AND INNOVATIVE TECHNOLOGIES - Oripova Malika Abdutolib qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the role of national imagery in visual arts education and examines the use of didactic materials and innovative technologies to enhance learning outcomes. National imagery reflects cultural identity, historical heritage, and aesthetic values, making it a vital component of art education. The study highlights pedagogical strategies for incorporating national motifs into lessons, using both traditional didactic resources and modern technological tools. Integrating innovative methods with culturally significant content fosters creativity, artistic competence, and cultural awareness among students, contributing to a more effective and engaging educational process.